To solve for x in the equation 13x + 24 = 3x - 26, we need to simplify and isolate the variable x.
First, let's combine like terms by subtracting 3x from both sides of the equation:
13x - 3x + 24 = 3x - 3x - 26
10x + 24 = -26
Next, let's isolate the variable x by subtracting 24 from both sides of the equation:
10x + 24 - 24 = -26 - 24
10x = -50
Finally, divide both sides of the equation by 10 to solve for x:
(10x)/10 = -50/10
x = -5
Therefore, the solution to the equation is x = -5.
Solve for x: 13x+24=3x−26.
5 answers
Solve for x: −12x+20=−10x+32.
To solve for x in the equation -12x + 20 = -10x + 32, we will simplify and isolate the variable x.
First, let's combine like terms by subtracting -10x from both sides of the equation:
-12x + 10x + 20 = -10x + 10x + 32
-2x + 20 = 32
Next, let's isolate the variable x by subtracting 20 from both sides of the equation:
-2x + 20 - 20 = 32 - 20
-2x = 12
Finally, divide both sides of the equation by -2 to solve for x:
(-2x)/-2 = 12/-2
x = -6
Therefore, the solution to the equation is x = -6.
First, let's combine like terms by subtracting -10x from both sides of the equation:
-12x + 10x + 20 = -10x + 10x + 32
-2x + 20 = 32
Next, let's isolate the variable x by subtracting 20 from both sides of the equation:
-2x + 20 - 20 = 32 - 20
-2x = 12
Finally, divide both sides of the equation by -2 to solve for x:
(-2x)/-2 = 12/-2
x = -6
Therefore, the solution to the equation is x = -6.
Solve for x: 5x+2=3x−20.
To solve for x in the equation 5x + 2 = 3x - 20, we will simplify and isolate the variable x.
First, let's subtract 3x from both sides of the equation:
5x - 3x + 2 = 3x - 3x - 20
2x + 2 = -20
Next, let's isolate the variable x by subtracting 2 from both sides of the equation:
2x + 2 - 2 = -20 - 2
2x = -22
Finally, divide both sides of the equation by 2 to solve for x:
(2x)/2 = -22/2
x = -11
Therefore, the solution to the equation is x = -11.
First, let's subtract 3x from both sides of the equation:
5x - 3x + 2 = 3x - 3x - 20
2x + 2 = -20
Next, let's isolate the variable x by subtracting 2 from both sides of the equation:
2x + 2 - 2 = -20 - 2
2x = -22
Finally, divide both sides of the equation by 2 to solve for x:
(2x)/2 = -22/2
x = -11
Therefore, the solution to the equation is x = -11.